Sugarcane tolerance to ratoon eradication with glyphosate determined by physiological responses - Silva,M.A. (2014)
This study aimed to evaluate the tolerance of sugarcane cultivars to ratoon eradication under different glyphosate rates by means of physiological responses. Therefore, a trial was carried out in randomized complete blocks with 4 x 4 factorial design (cultivars x rates) totaling 16 treatments with four replicates. The cultivars IAC91-5155, IACSP93-3046, and IAC86-2480 and IAC87-3396 and the glyphosate rates 0 g ha-1; 1,920 g ha-1; 2,400 g ha-1; 2,880 g ha-1 were tested. The variables analyzed were percentage of tiller mortality, quantum efficiency of PSII (Fv/Fm) and SPAD index. The results showed that there are differences among sugarcane cultivars for tiller eradication and for physiological responses with glyphosate different rates. The rate of 2,880 g ha-1 was the most efficient in eliminating sugarcane tillers. The cultivars IAC86-2480, IAC87-3396 and IACSP93-3046 were the most sensitive and the IAC91-5155 tolerated, for a longer period of time, the damage to the photosynthetic apparatus of the ratoons caused by glyphosate desiccation. Due to different responses, different managements should be considered for eliminating ratoons of different cultivars.